Estágio supervisionado obrigatório carcinoma de células escamosas oral em cão: relato de caso - Silva, Francisco Herbeson Aquino (Universidade Federal Rural do Semi-Árido, 2021)
This paper describes the activities carried out during the Mandatory Supervised Internship (ESO), with the objective of monitoring the routine of clinical and surgical care, in order to develop and improve practical skills. This work also aimed to report a case of squamous cell carcinoma (SCC), followed up at the Animal Veterinary Clinic. SCC is a slow growing but locally invasive neoplasm that can affect any skin region. It is the second most common tumor in dogs, affecting more often animals aged between 10 and 11 years with light fur and depigmented skin. The patient was a 3-year-old, neutered, black-coated Belgian Shepherd dog weighing 35 kg. The only clinical manifestation presented was a red lesion on the roof of the oral cavity that did not heal. Macroscopically, the lesion had an irregular contour, reddish color, no bleeding and an ulcerated appearance. Biopsy, pre surgical exams, electrocardiogram and echocardiogram were requested. The result of the histopathological exam confirmed the suspicion, being diagnosed with squamous cell carcinoma. The report contained atypical epithelial cell proliferation with moderate pleomorphism, eosinophilic cytoplasm, anisocariosis, coarse chromatin and evident nucleoli. The treatment instituted was cryotherapy, with application of liquid nitrogen for 10 seconds and maintenance of the frozen tissue for 60 seconds, in three cycles with intervals of 3 minutes. Therefore, due to the increase in the number of cases of this neoplasm in small animal clinics, the veterinarian must conduct the most effective treatment to restore the patient's quality of life.
Keywords: Biópsia; Cão; Criocirurgia; Neoplasia; Palato; CIENCIAS AGRARIAS::MEDICINA VETERINARIA